ACCEPTANCE IN USING ELECTRONIC PAYMENT SYSTEM OF WORKING PEOPLE IN THE CENTRAL REGION, THAILAND - ขันธเขตต์ วิวัฒณ์; ฉวีสุข สิงหะ (Journal of KMITL Business school, 2019)
Electronic payment is a type of technology system that plays a significant role in the current economic system. This research aimed to study the level of acceptance of using electronic payment systems of working people groups gathered data by choosing the central region of Thailand. The objective was to study the level of electronic payment systems acceptance by demographic factors among working people groups in the central region of Thailand. There were 400 samples for this research which was used the independent samples t-test and One-Way ANOVA analytic methods. The analysis results found that for the working-age with different gender accepted of electronic payment systems, there were no significant differences in opinions. Indicated by differences in education, occupation and average of net income at least one (1) pair of significance was found from the testing assumption. Grouping with income levels more than 45,001 baht with the level of acceptance of electronic payments is significantly different from the group with an income level below or equal to 15,000 baht significantly at the level of 0.05. This research might be more beneficial to particular institutions, financial institutions, in using information to develop a system with speed and safety in receiving and paying of electronic payment systems.